2021
DOI: 10.3390/cancers13215292
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and Relative Handgrip Strength as Indicators of Self-Reported Physical Function and Quality of Life in Breast Cancer Survivors: The EFICAN Study

Abstract: Background: Although breast cancer (BC) is the most prevalent type of cancer in the world, its high survival rate implies that many people live long after the treatments and face their side effects. The physical function (PF) and health-related quality of life (HRQoL) of people surviving BC decreases significantly, which makes important to identify markers that may be associated with a better health status and prognosis. Previous studies suggest that handgrip strength (HGS) and HGS relative to the body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In a prospective population-based follow-up study, Taekema et al [ 17 ] showed that poor handgrip strength predicted impaired ADL and cognitive decline in 555 older adults aged 85 years and older in the Netherlands. Additionally, previous studies have reported that handgrip strength is an important determinant of HRQoL in cancer survivors in Korea [ 21 ] and Spain [ 22 ]. Taken together, the findings from the current and previous studies support the prognostic roles of anemia and weak handgrip strength in identifying poor HRQoL later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective population-based follow-up study, Taekema et al [ 17 ] showed that poor handgrip strength predicted impaired ADL and cognitive decline in 555 older adults aged 85 years and older in the Netherlands. Additionally, previous studies have reported that handgrip strength is an important determinant of HRQoL in cancer survivors in Korea [ 21 ] and Spain [ 22 ]. Taken together, the findings from the current and previous studies support the prognostic roles of anemia and weak handgrip strength in identifying poor HRQoL later in life.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, loss of muscle strength assessed by handgrip strength is associated with health conditions, sarcopenia, disability, impaired physical functioning, and cognitive decline in older adults [ 17 ]. Additionally, handgrip strength is a biomarker for a lower HRQoL in older populations [ 18 , 19 , 20 ] and cancer survivors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further physical health-related challenge breast cancer survivors often face is changes in their appearance, such as weight loss. According to research, cancer therapy causes weight fluctuations, as well as changes in skin and nail color (13). Breast cancer survivors often feel embarrassed, lose their confidence, and have body image problems due to their changed appearance.…”
Section: Overcoming Health Problems In Breast Cancer Survivorsmentioning
confidence: 99%
“…HGS is a predictor of mortality and length of hospital stay [36]. This measurement is widely used to assess older individuals and cancer patients [37,38]. The HGS test was performed according to the guidelines established by the American Society of Hand Therapists [39] using a hand hydraulic dynamometer (JAMAR, Sammons Preston Rolyan, Bolingbrook, IL, USA).…”
Section: Hand Grip Strength (Hgs) Testmentioning
confidence: 99%